AB0396 Infliximab and Adalimumab Levels and Antidrug Antibodies Detection in Patients with Rheumatoid Arthritis (RA): an Interlaboratory Comparison Using A Commercial ELISA Assay. (10th June 2014) - Valor, L.; Hernández Flόrez, D.; de la Torre, I.; Llinares, F.; Rosas, J.; Yaque, J.; Naredo, E.; Gonzalez, C.; Lόpez-Longo, J.; Monteagudo, I.; Montoro, M.; Carreño Perez, L.
Abstract : Background: The assessment of biological drug levels and immunogenicity might be essential in terms of a more effective and rational use of biological therapies and it is dependent upon the establishment of efficient standardized assays or a consensus that could allow a direct comparison of drug levels and anti-drug antibodies (ADA) data with clinical outcome. Objectives: To determine whether an enzyme-linked immunosorbent assay (ELISA) performed with two versions of a commercial kit to assess IFX and ADL levels and ADA yield similar results. Methods: The diagnostic capability of two ELISA versions [Promonitor® IFX R1 and R2 (V.1), Promonitor® IFX and Anti-IFX (V.2); Promonitor® ADL R1 and R2 (V.1), Promonitor® ADL and Anti-ADL (V.2) kits (Progenika Biopharma, Spain)] was evaluated in patients with RA treated either with infliximab (IFX; n=24) or adalimumab (ADL; n=24) by three different laboratories. The reliability was determined using the Cohen's Kappa coefficient (K), the Pearson's r, the intraclass correlation coefficient (ICC) and the Lin's concordance correlation coefficient (CCC). The Bland-Altman plots of differences between V.1 and V.2 were drawn to compare values of each assay. Results: The qualitative discordant results for IFX levels V.1 were 9/24 samples (K= good) and 2/23 V.2 (K= very good), for ADL levels V.1 were 7/24 (K= moderate) and for V.2 were 0/24 (K= very good). For IFX-ADA were 0/24 in V.1 and V.2 (K= excellent), while for ADL-ADA were 1/24 in V.1 and 4/24 in V.2 (K= from very good to good). The quantitative agreement is shown in table 1, we found a good linear association using the Pearson's r, the ICC was questionable to excellent for both versions in IFX and ADL levels. The CCC results were poor in all determinations. Bland-Altman plots for both, IFX and ADL levels demonstrate the differences between both versions (Fig. 1 and 2, respectively). Conclusions: We observed a better agreement in the qualitative than in the quantitative results in both, for IFX and ADL levels and for IFX-ADA and ADL-ADA. We have found a good linear association (Pearson's r) but a low agreement (K, ICC and CCC) comparing results for V.1 and V.2. Further interlaboratory investigations are necessary to improve results and determine their possible clinical application. Disclosure of Interest: L. Valor: None declared, D. Hernández Flόrez: None declared, I. de la Torre: None declared, F. Llinares: None declared, J. Rosas: None declared, J. Yaque: None declared, E. Naredo Grant/research support: UCB and MSD, Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, C. Gonzalez: None declared, J. Lόpez-Longo: None declared, I. Monteagudo Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, MSD and Esaote, M. Montoro: None declared, L. Carreño Perez: None declared DOI: 10.1136/annrheumdis-2014-eular.3290